Fibrin Down-regulates LPS- and PMA-induced Tissue Factor Expression by Blood Mononuclear Cells - Rossiello, Maria Rosaria; Italia, Alessandra; Stramaglia, Anna M.; Gesualdo, Loreto; Grandaliano, Giuseppe; Schena, Francesco P.; Semeraro, Nicola; Colucci, Mario (Thrombosis and Haemostasis, 2000)
Several studies indicate that fibrin may play a functional role in inflammation by modulating a variety of cellular functions. We investigated the effect of fibrin on tissue factor (TF) production by blood mononuclear cells (MNC). Citrated human blood was recalcified and incubated at 37° C for 1-4 h. The resulting clot was lysed by the addition of tissue plasminogen activator (t-PA) and MNC were isolated by density gradient centrifugation. A control blood sample was processed in the same way but omitting calcium addition and clot formation. Clot-and blood-derived MNC did not express detectable TF activity and antigen whatever the incubation time. Clot-derived MNC, however, generated on average 5 fold less TF (activity and antigen) than control cells, when stimulated with lipopolysaccharide (LPS, 1 µg/ml) for 3 h at 37° C. A reduced TF response of clot-derived cells was also observed at mRNA level as indicated by RT-PCR and in situ hybridization. The effect was dependent on the incubation time within the clot, could not be reversed by enhancing LPS concentration or by adding serum, and was maintained if LPS was replaced by the tumor promoter PMA. A reduced TF response was also found when washed MNC were incorporated for 1 h at 37° C within purified fibrin but not when the cells were incubated with fibrinogen, thrombin or fibrin split products alone, indicating that contact with fibrin was responsible for the inhibition of TF production. Fibrin-induced down-regulation of TF response to LPS and PMA by MNC may represent a negative feed-back aimed at limiting excessive blood clotting activation in immuneinflammatory diseases.
Keywords: Fibrin; leukocytes; coagulation; tissue factor